Christ, Torah, and the Faithfulness of God: The Concept of Supersessionism in “The Gifts and the Calling” - Tapie, Matthew (Studies in Christian-Jewish Relations, 2017)
This article analyzes usage of the term “supersessionism,” in the December 2015 document authored by the Pontifical Commission for Religious Relations with the Jews, and entitled, “The Gifts and the Calling of God are Irrevocable: A Reflection on Theological Questions Pertaining to Catholic-Jewish Relations on the Occasion of the 50th Anniversary of Nostra Aetate” (No.4). After setting the document in the context of postconcilar Catholic reflection on Jews and Judaism, the article argues that while “Gifts and the Calling” provides important guidance for theological reflection, the document does not identify supersessionism with necessary precision. Drawing upon the thought of the French-Jewish historian Jules Isaac, and the Methodist theologian R. Kendall Soulen, the article demonstrates how their critical remarks about a particular Christian teaching regarding Christ’s fulfillment of Jewish law greatly clarifies the language of supersessionism for the Catholic-Jewish dialogue.